Design of a Business Hotel in Grand Batang City with a Sustainable Architecture Approach - Ivanka Abnajapa; Moch. Fathoni Setiawan; Didik Nopianto Agung Nugradi (Universitas Negeri Semarang, 2025)
Grand Batang City is an integrated industrial area located in Batang Regency, Central Java. As this industrial zone develops, Batang Regency is positioning itself to become a business hub for investors who need long-term accommodation to manage their operations. This phenomenon has led to increased demand for accommodation and meeting venues to host business visits from investors, trade partners, and professionals, as well as to support industry conferences and a surge in demand for lodging and meeting venues to accommodate business visits from investors, trade partners, and professionals, as well as to support industry-related conferences. The current problem requires urgent attention because, according to current data, Batang Regency hotels do not have essential business facilities. The research provides an architectural design framework that establishes a sustainable business hotel design plan. This approach blends functional requirements, site context, and eco-friendly design strategies to support business activities efficiently and sustainably.